PRINSIP-PRINSIP MANAJEMEN PENDIDIKAN DALAM HADIS - Hairul Hudaya (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
The Prophet Muhammad Saw has a great influence among his best friends. The influence was also felt in the field of management education. In management, there are four principles: planning, organizing, actuating and controlling. These four elements are then adopted in managing educational institutions which so called educational management. These four principles are also found in the prophetic spirit. In the beginning of the reign of the Prophet Muhammad in Medina, he launched a literacy program for the companions which was followed by the instructions to the particular person to learn certain science. The Prophet also established teaching and learning for all his followers. During the study, he often asked questions to know how far the companions’ mastery of the material being taught. What the Prophet did can be categorized as a principle of prophetic management based education.